Retrospective Evaluation of the Antibody Prevalence in Epilepsy and Encephalopathy (APE2) Score. (5th January 2022) - Poore, Brad; Hamilton, Robert; Kelliher, Michael T; Mahmood, Sundis; Mindiola-Romero, Andres E; Richards, Ryland; Motanagh, Samaneh; Cervinski, Mark A; Nerenz, Robert D
Abstract: Background: Autoimmune encephalitis (AE) is a rare collection of disorders that present with a diverse and often nebulous set of clinical symptoms. Indiscriminate use of multi-antibody panels decreases their overall utility and predictive value. Application of a standardized scoring system may help reduce the number of specimens that generate misleading or uninformative results. Methods: The results of autoimmune encephalopathy, epilepsy, or dementia autoantibody panels performed on serum (n = 251) or cerebrospinal fluid (CSF) (n = 235) specimens from October 9 th, 2016 to October 11 th, 2019 were collected. Retrospective chart review was performed to calculate the Antibody Prevalence in Epilepsy and Encephalopathy (APE 2 ) score for patients with an antibody above the assay-specific reference interval and to classify results as true or false positive. Results: Of the 486 specimens, 60 (12.3%) generated positive results for any AE antibody (6 CSF and 54 serum). After removing 2 duplicate specimens collected from a single patient, 10 of the remaining 58 were determined to be true positives and 8 contained neural-specific antibodies. Application of the APE 2 score revealed that 89% of all true positives and 86% of specimens with neural-specific antibodies had a score ≥4. In contrast, 76% of false positives, 74% of clinically nonspecific antibodies, and 85% of the negative specimens had an APE 2 score <4. Conclusion: The APE 2 score can improve the diagnostic utility of autoimmune encephalopathy evaluation panels.